Current State of Ontology Matching. A Survey of Ontology and Schema Matching - Mukkala Lauri; Arvo Jukka; Lehtonen Teijo; Knuutila Timo (University of Turku Technical Reports, 2022)
Ontology matching is an important task when data from multiple data sources is integrated. Problems of ontology matching have been studied widely in the researchliterature and many diﬀerent solutions and approaches have been proposed alsoin commercial software tools. In this survey, well-known approaches of ontologymatching, and its subtype schema matching, are reviewed and compared. The aimof this report is to summarize the knowledge about the state-of-the-art solutionsfrom the research literature, discuss how the methods work on diﬀerent application domains, and analyze pros and cons of diﬀerent open source and academic tools inthe commercial world.